2003
DOI: 10.1128/mcb.23.9.3173-3185.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role for Human SIRT2 NAD-Dependent Deacetylase Activity in Control of Mitotic Exit in the Cell Cycle

Abstract: Studies of yeast have shown that the SIR2 gene family is involved in chromatin structure, transcriptional silencing, DNA repair, and control of cellular life span. Our functional studies of human SIRT2, a homolog of the product of the yeast SIR2 gene, indicate that it plays a role in mitosis. The SIRT2 protein is a NADdependent deacetylase (NDAC), the abundance of which increases dramatically during mitosis and is multiply phosphorylated at the G 2 /M transition of the cell cycle. Cells stably overexpressing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
383
3
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(408 citation statements)
references
References 46 publications
15
383
3
7
Order By: Relevance
“…Synthetic 11-mer H3 peptide and acetylated H3 peptide (AcH3), corresponding to the 11 amino acids surrounding and including lysine-14 of the histone H3 N-terminal tail; H 2 N-KSTGGK (Ac)APRKQ-CONH 2 , were purchased from the University of Wisconsin-Madison peptide synthesis center, 3 H-labeled Acetyl H3-peptide ( 3 H-AcH3) was synthesized enzymatically from the 11-mer H3 peptide as previously reported (33). 18 O-labelled water was purchased from Cambridge Isotope Laboratories, Inc. (Andover, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Synthetic 11-mer H3 peptide and acetylated H3 peptide (AcH3), corresponding to the 11 amino acids surrounding and including lysine-14 of the histone H3 N-terminal tail; H 2 N-KSTGGK (Ac)APRKQ-CONH 2 , were purchased from the University of Wisconsin-Madison peptide synthesis center, 3 H-labeled Acetyl H3-peptide ( 3 H-AcH3) was synthesized enzymatically from the 11-mer H3 peptide as previously reported (33). 18 O-labelled water was purchased from Cambridge Isotope Laboratories, Inc. (Andover, MA).…”
Section: Methodsmentioning
confidence: 99%
“…SIRT2 is a histone deacetylase with a preference for histone H4 as a substrate [Vaquero et al, 2006], and has been shown to regulate mitotic exit [Dryden et al, 2003] and chromosomal condensation during mitosis [Vaquero et al, 2006;Inoue et al, 2007]. However, unlike the nuclear SIRT1, SIRT2 is more predominantly a cytoplasmic protein that colocalizes with microtubules [North et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…These genes comprise the sirtuins, orthologues of the yeast silent information regulator 2 (SIR2) family of genes. Sirtuins are a highly conserved set of genes found in organisms ranging from bacteria to man (Brachmann et al, 1995;Frye, 2000), involved in a variety of essential cell processes, including ageing, preventing differentiation, apoptosis and resistance to metabolic stress (Vaziri et al, 2001;Dryden et al, 2003). We have previously hypothesised that sirtuins, which link the functions of the mitochondrion, telomere nucleo-protein complex and ribosome production (the MTR), may be important contributors to a wide range of ageing related diseases including cancer (Shiels and Davies, 2003).…”
mentioning
confidence: 99%